Loss of ABHD5 promotes the aggressiveness of prostate cancer cells. Issue 1 (December 2017) - Chen, Guohua; Zhou, Guoli; Aras, Siddhesh; He, Zhenhui; Lucas, Stephanie; Podgorski, Izabela; Skar, Wael; Granneman, James; Wang, Jian
Abstract The accumulation of neutral lipids in intracellular lipid droplets has been associated with the formation and progression of many cancers, including prostate cancer (PCa). Alpha-beta Hydrolase Domain Containing 5 (ABHD5) is a key regulator of intracellular neutral lipids that has been recently identified as a tumor suppressor in colorectal cancer, yet its potential role in PCa has not been investigated. Through mining publicly accessible PCa gene expression datasets, we found that ABHD5 gene expression is markedly decreased in metastatic castration-resistant PCa (mCRPC) samples. We further demonstrated that RNAi-mediated ABHD5 silencing promotes, whereas ectopic ABHD5 overexpression inhibits, the invasion and proliferation of PCa cells. Mechanistically, we found that ABHD5 knockdown induces epithelial to mesenchymal transition, increasing aerobic glycolysis by upregulating the glycolytic enzymes hexokinase 2 and phosphofrucokinase, while decreasing mitochondrial respiration by downregulating respiratory chain complexes I and III. Interestingly, knockdown of ATGL, the best-known molecular target of ABHD5, impeded the proliferation and invasion, suggesting an ATGL-independent role of ABHD5 in modulating PCa aggressiveness. Collectively, these results provide evidence that ABHD5 acts as a metabolic tumor suppressor in PCa that prevents EMT and the Warburg effect, and indicates that ABHD5 is a potential therapeutic target against mCRPC, the deadly aggressive PCa.